Automatic verification of timed concurrent constraint programs - FALASCHI, MORENO; VILLANUEVA, ALICIA (Theory and practice of logic programming, 2006)
The language Timed Concurrent Constraint (tccp) is the extension over time of the Concurrent Constraint Programming (cc) paradigm that allows us to specify concurrent systems where timing is critical, for example reactive systems. Systems which may have an infinite number of states can be specified in tccp. Model checking is a technique which is able to verify finite-state systems with a huge number of states in an automatic way. In the last years several studies have investigated how to extend model checking techniques to systems with an infinite number of states. In this paper we propose an approach which exploits the computation model of tccp. Constraint based computations allow us to define a methodology for applying a model checking algorithm to (a class of) infinite-state systems. We extend the classical algorithm of model checking for LTL to a specific logic defined for the verification of tccp and to the tccp Structure which we define in this work for modeling the program behavior. We define a restriction on the time in order to get a finite model and then we develop some illustrative examples. To the best of our knowledge this is the first approach that defines a model checking methodology for tccp.